Editorial do V.4, N.1 - Câmara, Gabriel Guerra; de Gonçalves, Fernando Gonçalves; de Freitas, Gabriela Ramão; Lopes, Rodrigo de Macedo; Lopes, Ricardo Cortez; Martinez, Lis Yana de Lima; de Moura, Carolina Navarrina (Revista Contraponto, 2017)
Editorial dessa edição